The Impact of Entertainment on Buyers’ Decisions via Facebook: Jordanian Youth Behavior of E-Fashion Stores Context - Al-Nsour, Iyad A; Tarofder, Arun Kumar (Journal of Asian Business Strategy, 2022)
This study aims to determine the impact of social media entertainment on buying decisions via the Facebook platform. The research is quasi-experimental and is quantitative and descriptive. The sample size reached 500 active Facebook users from the Jordanian youth, and the snowball sample technique was employed. A questionnaire is the only tool used to collect the primary data and contains closed-ended questions. The Likert five-point scale measures the responses through the partial least squares (PLS) method. It was concluded that there is a positive statistical impact of social media-based entertainment on the buying decisions from e-fashion stores on the Facebook platform, and social media entertainment explains 28% of the variations in the buying decisions from e-fashion stores via Facebook. Social media is an effective and safe solution to cutting high unemployment rates in the Jordanian economy. The e-buying experience depends on entertainment, enjoyment, relaxation, and leisure. It is a radical solution for creating new jobs in the economy and decreasing the poverty rates among poor and unemployed people.